Linguoculturological Study of Archaism and Historicims in English and Karakalpak Language - Sultamuratovna, Seytmuratova Dilbar (European Journal of Life Safety and Stability (2660-9630), 2023)
Due to the fact that archaisms and historicism often reveal the possibilities of the figurativeness and expressiveness of our language, it is important to study the participation of linguoculturological aspects. Therefore, in English, Karakalpak linguistics, a number of works have been created. The article provides the importance of archaisms and historicism on linguaculture.